APLIKASI INFORMASI HARGA MATERIAL BANGUNAN DI TOKO SINAR JAYA DENGAN KODE QR BERBASIS ANDROID - Pardede, Uly; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2022)
ABSTRACTInformation is a service of data or facts that have been processed until it becomes something that easy to understand and can be useful for recipients as knowledge and decision makers. This information is a combination of technology where this activity uses technology to support operations and management.Material is finished building materials, which is ready to be used. Implementation of this material price information can be used to find out a material price when shopping. The application that will be designed is an application that uses a barcode scanning system to obtain information on the price of an item and will later be developed according to user needs. QR code stands for quick response code which is a two-dimensional barcode that can provide various types of information directy. The QR code consist of black dots and white spaces in the shape of a box. Android is an operating system or mobile-based operating system that is very popular today, especially on smartphones.The method used is the waterfall method,which means one type of application development model and is included in the classical life cycle which emphasizez systematic and sequential phases. In this study, blackbox testing was also carried out. Black box testing is a software testing method that tests functionality without looking at its internal structure or workings. This test method can be applied virtually to any level of software testing.Keywords: Android, Black box testing, Kode QR, Material